Competencies for governance of complex systems of systems. (14th April 2015) - Bradley, Joseph M.; Unal, Resit; Pinto, C. Ariel; Cavin, Edward S.
Systems of Systems (SoS) require organisational components to have staff with abilities appropriate to the challenges within SoS. Large organisations frequently use competency models as a tool to ensure that their staff have the proper skills to deal with these challenges. Competency models have been used for 40 years to select, train, promote or separate employees. While competency models represent an improvement on their primary predecessor, intelligence tests, weaknesses have been noted in the literature and challenges have been made to improve them. Most improvement efforts have been evolutionary adjustments or insertion of more elements. This research presents a completely new way to create, assess or transform a competency model. This framework can be used to design, assess or transform an existing competency model. This paper represents a significant expansion of a conference paper presented at SOSE 2014 in Adelaide, South Australia in June 2014.